2021
DOI: 10.32497/jrm.v16i2.2186
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Konsentrasi Pati dan Yeast pada Pembuatan Etanol dari Pati Sorgum Melalui Proses Simultaneous Saccharification and Fermentation (SSF) dan Separated Hydrolysis Fermentation (SHF)

Abstract: <p>Bioetanol merupakan anhydrous alkohol yang dapat diproduksi dengan cara fermentasi pati. Sorgum mengandung pati yang cukup tinggi sebesar 74,63g / 100g bahan sehingga dapat dimanfaatkan sebagai bahan baku pembuatan etanol. Pembuatan etanol berbahan baku pati sorgum ada dua metode yaitu Separated Hydrolysis Fermentation (SHF) dan Simultaneous Saccharification and Fermentation (SSF). Tujuan dari penelitian ini adalah menentukan proses yang tepat untuk memproduksi etanol dari pati sorgum dengan membandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Moreover, the ability of yeast to convert sugar is increased. In contrast to the research [16][17][18] that used a different fermentation raw material, namely sorghum starch, where the results of the study showed that the result of fermenting with the SSF method was more optimum compared to the SHF method. This can be seen from the concentration of ethanol produced with the SSF method resulted in a concentration in ethanol of 111,9 g/L with a 20% starch concentration used.…”
Section: Comparison Of Shf and Ssf Methods Based On Ethanol Productio...contrasting
confidence: 80%
“…Moreover, the ability of yeast to convert sugar is increased. In contrast to the research [16][17][18] that used a different fermentation raw material, namely sorghum starch, where the results of the study showed that the result of fermenting with the SSF method was more optimum compared to the SHF method. This can be seen from the concentration of ethanol produced with the SSF method resulted in a concentration in ethanol of 111,9 g/L with a 20% starch concentration used.…”
Section: Comparison Of Shf and Ssf Methods Based On Ethanol Productio...contrasting
confidence: 80%
“…Pretreatment was carried out by adding 0.1 M NaOH to corncob powder, which was then hydrolyzed using an HCl solution. The results showed that the higher the acid concentration, the higher the ethanol content obtained [12]. The production of bioethanol from lignocellulosic materials requires four main process units, namely pretreatment, to break down lignocellulosic bonds and separate lignin from cellulose and hemicellulose polymer chains.…”
Section: Bioethanol Manufacturing Processmentioning
confidence: 99%
“…The more enzymes added, the greater the level of bioethanol produced because more glucose is converted to bioethanol. Microorganisms grow and develop activities to change the fermented material into the desired product in the fermentation process [12]. The optimum process of fermentation depends on the type of organism; adding factors that affect the fermentation process are temperature, initial pH of fermentation, inoculum, substrate, and nutrient content of the medium.…”
Section: Fermentation Processmentioning
confidence: 99%